Shaping the City that Decreases Overweight and Obesity through Healthy Built Environment - MARIA A. EL HELOU (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
Cities are being built based on the concepts of comfortable, easy, and fast for the inhabitants. However, what is being constructed is promoting physical inactivity, and people are finding that what was being considered as convenient for daily life is, in fact, harmful to their physical health. This study points to the many components of a city that beats overweight issues and especially obesity. The case study is the city of Beirut: in-depth interviews were conducted with a representative sample of Beirutis (people whose families come from the Beirut city and who were born in this city and are still living in it). These interviews helped measure these participants’ satisfaction with the physical activities and social life that is accessible for all the inhabitants through inclusive urban planning (such as clean open spaces, parks, sidewalks, free or inexpensive public spaces, facilities for green transportation, etc.). The results of the analysis of the interviews were supported with past data demonstrating the increasing obesity issues in Lebanon and previous data in urban and psychological studies that expound the way the brain processes the urban spaces that increase satisfaction and the urban areas that the city should be offering to its inhabitants for positive health outcomes. The results uncovered the cycle of physical health, mental health, and social contacts which altogether affect the soul of a city where the aim is first and foremost the right to a healthy lifestyle.